Evidence-based rehabilitation after acquired brain injury: a clinical trial on a holistic neuropsychological rehabilitation program - Guerreiro, Sandra (2021)
Comprehensive-holistic neuropsychological programs have been recommended as a practice standard during post-acute rehabilitation in order to reduce cognitive and functional disability after moderate or severe brain injury. One major challenge of clinical research is to provide systematic data for the development of evidence-based neuropsychological rehabilitation. Rehabilitation after brain injury is concerned with reducing levels of disabil ity, either through restoration, or the use of adaptive and compensatory strategies. The goal of rehabilitation is not only the remediation of cognitive impairment, but mainly the establishment of a meaningfully and satisfactory life in face of persisting limitations. Outcomes may be assessed at the level of impairment, activity or participation. This study aims to evaluate the effi cacy of the Holistic Neuropsychological Rehabilitation Program (HNRP), held in Centro de Reabilitação Professional de Gaia in cognitive perform ance, emotional stability, functional ability and quality of life.